Numerical simulation of the pedestrian comfort of the microdistrict - Olga Poddaeva; Pavel Churin (Energy Reports, 2022)
This article is concerned with the questions of assessment of microdistrict pedestrian comfort associated with wind influences. The application of the generic methodology developed by the authors for assessing the wind influences in respect of the assigned task is presented. Researched are the questions of pedestrian comfort assessment in a microdistrict that has been already built with heightened comfort requirements (this is the concept “Yard without Cars”) and originally disadvantageous location in terms of aerodynamics which heavily reduces the possibilities of comfort compensation by modifying the microdistrict layout during the design phase. A 3D computer model of the facility is built. The numerical simulation is carried out using the ANSYS software. The numerical grid parameters, boundary commissions, and computation technology are set out. The streamlines for various wind directions are obtained. For a pedestrian comfort assessment, the stream velocity modulus distributions are analyzed in relation to the flow field. Using the Qcritparameter distribution, the stream velocity distribution may be obtained at any values of wind velocity. On the basis of the obtained results, the pedestrian comfort of the space in the territory of a residential complex was researched at any wind direction.